2006
DOI: 10.1111/j.1551-2916.2006.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ultrathin‐Walled Carbon‐Based Nanoporous Structures by Etching Pseudo‐Amorphous Silicon Oxycarbide Ceramics

Abstract: Etching polymer‐derived silicon‐oxycarbide ceramics with hydrofluoric acid creates nanoporous structures of specific surface areas as high as 600 m2/g. The change in composition upon etching shows the removal of silica, not carbon. The structure remaining after etching is postulated to consist of a scaffolding of graphene networks with their surfaces decorated with mixed bonds of tetrahedral silicon bonded to both oxygen and carbon (SiOmC4−m, where m=1, 2, or 3). The pores existing within such scaffoldings are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
55
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 30 publications
14
55
0
Order By: Relevance
“…The presence of amorphous silica cannot be excluded and most likely the major peak of this phase was superimposed with the broad reflections of disordered carbon in the given patterns. Both XRD patterns are in agreement with literature data reported for low and high carbon SiOC materials [22].…”
Section: Ch 4 /H 2 Storagesupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of amorphous silica cannot be excluded and most likely the major peak of this phase was superimposed with the broad reflections of disordered carbon in the given patterns. Both XRD patterns are in agreement with literature data reported for low and high carbon SiOC materials [22].…”
Section: Ch 4 /H 2 Storagesupporting
confidence: 92%
“…Studies on Si(O)C fibers reported CDC coatings, but no information on pore structure has been reported [19,20]. Albeit, it was shown that if a SiOC glass is etched for a long time (6 h) with a highly concentrated HF solution ($20%), the silica phase can be extracted leaving behind a highly porous oxycarbide-derived carbonaceous material containing SiC crystallites and Si atoms bonded to carbon, with SSA values as high as 700 m 2 /g and high pore volume up to 1.2 cm 3 /g [21,22]. It is important to note that this material can be derived from commercially available, inexpensive, easy to handle and versatile precursors such as polysiloxanes.…”
Section: Introductionmentioning
confidence: 96%
“…3.5 nm, which is in agreement with the results published by Peña-Alonso et al for etched SiOC glasses. 40 Our results suggest that the carbon content and its distribution in the hybrid material, and therefore, the PDMS, plays an important role on the phase development of the SiOC glass. The addition of iPrOH removes the highest amount of PDMS from the hybrid network.…”
Section: Discussionmentioning
confidence: 92%
“…The mixed bond tetrahedron may play a critical role in the performance and properties of SiCN and other polymer derived ceramics with similar nano-domains structures. After etching polymer-derived silicon-oxycarbide ceramics with hydrofluoric acid, silica domains are removed and the remaining structure is postulated to consist of a scaffolding of graphene networks with their surfaces decorated with mixed bonds of tetrahedral silicon bonded to both oxygen and carbon (Peña-Alonso et al, 2006). In Baek's study using SiCN as candidate for anode of Li-ion batteries to replace graphite anodes (Baek et al, 2014), the mixed bond tetrahedra of Si in SiCN is believed to act as an additional lithiation site.…”
Section: Resultsmentioning
confidence: 99%